Impact of dental treatment on the oral health-related quality of life of Brazilian schoolchildren - Jordanna Guedes Amorim Mendonça; Raquel Francis Almeida; Soraya Coelho Leal; Ítalo de Macedo Bernardino; Leandro Augusto Hilgert; Ana Paula Dias Ribeiro (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: This before-after experimental study evaluated the impact of dental treatment on the oral health-related quality of life (OHRQoL) in children aged 6-8 years from Paranoá, DF, considering the presence or absence of cavitated dentin carious lesions pre- and post-treatment. The responsiveness and sensitivity of the questionnaires were also investigated. Caries was detected by using the Caries Assessment Spectrum and Treatment (CAST) instrument, while the impact of oral health on the children's health-related quality of life was assessed using the Brazilian version of the Child Perceptions Questionnaire (CPQ8-10), which was completed by the children and the Brazilian version of the Early Childhood Oral Health Impact Scale (B-ECOHIS), which was completed by their parents. Sociodemographic characteristics were also assessed. After the examinations, the children were categorized into two groups according to the presence (treatment/n = 34) or absence (control/n = 34) of cavitated dentin carious lesions. Restorative/curative care was provided to the treatment group, while the control group received preventive measures. OHRQoL was assessed at baseline and at four weeks post-treatment. No significant sociodemographic differences were observed between the groups. In the treatment group, the children and their families reported a greater impact of oral health on their OHRQoL in both questionnaires (p < 0.05). However, there was a significant reduction in the impact of oral health, with differences between the pre-treatment and post-treatment phases (p = 0.001). Good sensitivity and responsiveness were observed for both questionnaires. Dental treatment was found to reduce the negative impact of dental caries on OHRQoL in 6-8-year-old children, which was detected by both questionnaires (B-ECOHIS and CPQ8-10).